Faktor-Faktor yang Mempengaruhi Financial Distress di Masa Pandemi Covid-19 - Indah Larassati Indah Larassati; Ratna Septiyanti; Widya Rizki Eka Putri (Universitas Widyatama, 2022)
This study explains relationship between financial distress and the factors that influence it by using property and real estate companies listed on the Indonesia Stock Exchange in 2020 as the unit of analysis. This study highlights the factors that affect financial distress during the COVID-19 pandemic. This study raised the issue of covid-19 during 2020. This study found that the Debt to Equity Ratio had a significant positive effect on financial distress, Net Profit Margin had a significant negative effect on financial distress, the Current Ratio had an insignificant negative effect on financial distress and Inventory Turnover had a significant negative effect. to financial distress.